99 cent: Price Points in E-Commerce - Franz Hackl; Michael E. Kummer; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2010)
Basu (2006) argues that the prevalence of 99 cent prices in shops can be explained with rational consumers who disregard the rightmost digits of the price. This bounded rational behaviour leads to a Bertrand equi- librium with positive markups. We use data from an Austrian price com- parison site and find results highly compatible with Basu's theory. We can show that price points - in particular prices ending in 9 - are preva- lent and have significant impact on consumer demand. Moreover, these price points are sticky; neither the price-setter itself wants to change them neither the rivals do underbid these prices, if they represent the cheapest price on the market.
Keywords: M31; L81; L25; 330; e-commerce; price comparison; price policy; Preiswettbewerb; Betriebliche Preispolitik; Konsumentenverhalten; E-Business; Österreich